2017
DOI: 10.1080/2162402x.2017.1343775
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade augments anti-neuroblastoma immune response induced by anti-GD2 antibody ch14.18/CHO

Abstract: Immunotherapy with anti-GD antibody (Ab) ch14.18/CHO is effective for treatment of high-risk neuroblastoma (NB) patients and is mainly based on GD-specific Ab-dependent cellular cytotoxicity (ADCC). Strategies to further enhance the efficacy are important and currently explored in prospective clinical trials randomizing ch14.18/CHO ± IL-2. Recently, expression of programmed death 1 (PD-1) inhibitory receptor by effector cells and its ligand (PD-L1) by tumor cells has been shown. Here, we report for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 24 publications
(51 reference statements)
3
61
0
2
Order By: Relevance
“…Nevertheless, the potency of CPis to induce a more potent anti-tumor immune response, and therefore potential induction of anti-tumor immunological memory, makes checkpoint inhibition a very interesting candidate as an adjuvant therapy in curative treatment settings. The utilization of CPis as a monotherapy in NBL has been investigated in multiple pre-clinical studies [42,[111][112][113]. These studies show no effect of CPi treatment on systemic NBL progression in vivo.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the potency of CPis to induce a more potent anti-tumor immune response, and therefore potential induction of anti-tumor immunological memory, makes checkpoint inhibition a very interesting candidate as an adjuvant therapy in curative treatment settings. The utilization of CPis as a monotherapy in NBL has been investigated in multiple pre-clinical studies [42,[111][112][113]. These studies show no effect of CPi treatment on systemic NBL progression in vivo.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…Next to these observations, especially studies investigating CPi-including combination therapies revealed some insights in mechanisms explaining NBL resistance to CPi monotherapy [42,[111][112][113]. Rigo and colleagues showed that combining CPi with temporary CD4 depletion by anti-CD4 monoclonal antibody (mAb) treatment caused a very potent CD8 T cell dependent response causing significantly longer tumor-free survival, complete tumor regression, and durable anti-NBL immunity in vivo [111].…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to injection into mice, NXS2-HGW tumor cells were analyzed for NB-specific characteristics[ 31 ]. Gene-specific RT-PCR analysis revealed a strong mRNA expression of the TAA TH (175 bp; Fig 3A ), underlining the applicability of this model to investigate the TH-directed immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Syngenic PD-L1 + /GD2 + NB-bearing mice treated with ch14.18/CHO combined with anti-PD-1 mAb showed a strong reduction of tumor growth, prolonged survival, and the highest cytotoxicity against NB cells. These data suggested that the combination of ch14.18/CHO with PD-1 blockade may represent a new effective treatment strategy against GD2-positive cancers [ 51 ].…”
Section: Neuroblastomamentioning
confidence: 99%